Within-visit SBP variability from childhood to adulthood and markers of cardiovascular end-organ damage in mid-life. Issue 9 (September 2021) - Meng, Yaxing; Magnussen, Costan G.; Wu, Feitong; Buscot, Marie-Jeanne; Juonala, Markus; Pahkala, Katja; Hutri-Kähönen, Nina; Kähönen, Mika; Laitinen, Tomi; Viikari, Jorma S.A.; Raitakari, Olli T.; Sharman, James E.
Abstract : Background: Within-visit SBP variability is associated with age and SBP, but its long-term clinical significance is unknown. We examined the association between child, adult, and life-time within-visit SBP variability with markers of end-organ damage using data from a 31-year longitudinal study. Methods: Within-visit SBP variability was calculated as the standard deviation of three sitting SBP readings among up to 3010 participants aged 6–18 years (childhood) who were re-measured up to seven times to mid-adulthood. Markers of cardiovascular end-organ damage in adulthood were carotid intima--media thickness, brachial flow-mediated dilatation, carotid distensibility, pulse wave velocity, left ventricular mass index, carotid plaque, and coronary artery calcification. Results: The mean (standard deviation) cumulative within-visit SBP variability was 2.7 (1.5) mmHg in childhood, 3.9 (1.9) mmHg in adulthood and 3.7 (1.5) mmHg across the observed life-time. Childhood within-visit SBP variability was not correlated with its subsequent values measured from 3 to 31 years later. With adjustment for age, sex, cumulative SBP, BMI and serum lipids, neither child, adult, or life-time cumulative within-visit SBP variability associated with markers of cardiovascular end-organ damage. However, higher child, adult, and life-time cumulative SBP significantly associated with higher carotid intima--media thickness, higher pulse wave velocity, lower brachial flow-mediated dilatation, lower carotid distensibility in adulthood. Conclusion: Within-visit SBP variability from childhood to adulthood does not provide additional predictive utility over SBP over the same period of the life course. Abstract : Supplemental Digital Content is available in the text